Peningkatan Ekonomi Masyarakat Melalui Pemetaan Sumber Daya Alam Desa Bale Kecamatan Oba Kota Tidore - Zainal Abidin Marasabessy; Rina Jabar; Siti F. Maskur; Hasni Senen; Widyawati Diti (Janaka, Jurnal Pengabdian Masyarakat, 2022)
Mapping natural resources is very necessary for every region, including villages. This is very useful for mapping how many natural resources the area or village has, so that these natural resources can later be processed and used to generate economic income for local villagers. Through community service activities based on asset-based community development organized by the State Islamic Institute Ternate, which were carried out in Bale Village, Oba District, and Tidore City Islands, we tried to map the assets of Oba village. The village's assets are sourced from human and natural resources. Oba Village itself has a lot of potential natural wealth. The problem that occurred in Bale Village was that the community did not know how to manage village assets. One way out is the existence of a government program that can help the Oba village community in managing their natural wealth in the form of training in various skills, such as coffee processing and the processing of village assets in the form of village-owned buildings, all of which have economic value both for the village community and for the village government.